An exploratory study of clinical and physiological correlates of problematic social media use in adolescents - Shafi, Reem M.A.; Nakonezny, Paul A.; Miller, Keith A.; Desai, Jinal; Almorsy, Ammar G.; Ligezka, Anna N.; Morath, Brooke A.; Romanowicz, Magdalena; Croarkin, Paul E. (Psychiatry research, 2021)
•Problematic social media use in adolescents is a common clinical concern.•This study examined potential risk factors of problematic social media use.•Depression symptom severity was associated with increased risk.•Depressed females may have an increased risk of problematic social media use.•Elevated cortisol was associated with problematic use in adolescents. Prior validation studies of the Bergen Social Media Addiction Scale (BSMAS) demonstrate its utility for identifying problematic social media use in adolescents. There are knowledge gaps regarding the potential clinical and physiological underpinnings of problematic social media use in adolescents. This cross-sectional, single-visit study examined a sample of depressed (n = 30) and healthy (n = 30) adolescents who underwent clinical assessments of depressive symptom severity, bullying, cyberbullying, self-esteem, salivary measures of stress (cortisol and α-amylase) to identify correlates with adolescent and parental reports of the BSMAS. LASSO-penalized multiple linear regression models were implemented. With respect to the adolescent BSMAS scores in all subjects, the risk of problematic social media increased as depressive symptom severity increased. Depressed female adolescents appeared to have a greater risk. Based on parental BSMAS scores, depression status, depressive symptom severity, cyberbullying score, and salivary cortisol significantly predicted problematic social media use. For the depressed sample, the risk of problematic social media use increased as salivary cortisol increased. No significant predictors of problematic social media usage emerged in the healthy control sample. These preliminary results provide novel insights into clinical and physiological characteristics of problematic social media use in adolescents.